Thromboembolic Disease – Critical Evaluation of Laboratory Investigation - Malm, Johan; Laurell, Martin; Nilsson, Inga Marie; Dahlbäck, Björn (Thrombosis and Haemostasis, 1992)
Previous studies of patients with thromboembolic disease have revealed an association either with hereditary anticoagulant protein deficiencies or with defects in the fibrinolytic system. To obtain a more comprehensive picture and to investigate which analyses are useful in the evaluation of such patients, we have performed an extensive laboratory investigation in 439 individuals with thromboembolic disease. Anticoagulant protein deficiencies were found in 24 patients. Deficiencies of protein C (n = 10) and protein S (n = 9) were most common followed by deficiencies of antithrombin III (n = 3) and plasminogen (n = 2). Six of the nine protein S deficient patients demonstrated a selective deficiency of free protein S with normal total protein S concentrations. To diagnose protein C and S deficiencies among the 201 patients receiving oral vitamin K antagonists, the concentrations of protein C and S were compared with the mean concentration of several other vitamin K-dependent proteins. One protein C and three protein S deficiencies were identified among the treated patients. The number of protein C deficiencies found in this group was significantly lower than the number found among untreated patients. Although fewer protein S deficiencies were also identified among the treated patients, than in the untreated group, the difference was not statistically significant. The results suggest that protein C deficiencies went undetected in the treated group and that oral anticoagulant therapy should be discontinued before efforts to diagnose protein C deficiency are made. We found no cases with heparin cofactor II deficiency. Lupus anticoagulant was present in 10 patients. Evaluation of the fibrinolytic system revealed that the patient group had slightly lower mean euglobulin fibrinolytic activity (EFA) after venous occlusion than controls and a subgroup (approximately 15%) of patients with EFA below the level of the 5th percentile of controls, could be distinguished. Repeated analysis demonstrated a substantial individual day-to-day variation in both patients and controls and the combined EFA results did not clearly distinguish patients from controls. There was a significant negative correlation between EFA and plasminogen activator inhibitor (PAI) levels in both patients and controls and the patient group had significantly higher levels of PAI than the control group. In contrast, there was no difference between controls and patients in tissue plasminogen activator (tPA) release after venous occlusion and no correlation between EFA and tPA was observed. These results suggest that although a statistically significant difference between patients and controls in values of fibrinolytic parameters was found, an extensive laboratory evaluation of the fibrinolytic system in individual patients may not be warranted. The association between patients with thrombosis and deficiencies of anticoagulant proteins suggests that the investigation of individual patients should focus on these components.